Antimicrobial activities of a multi-species probiotic ingredient derived from opaque sorghum beer during its propagation in a starchy career model - CHABI, Ifagbémi Bienvenue; KAYODE, A. PIERRE POLYCARPE; AGBOBATINKPO, B.; VIEIRA-DALODE, Générose; ADENILE, A.; BABA-MOUSSA, LAMINE; CODJIA, J.T.C. (My University, 2016)
This study evaluates the antimicrobial activities of a multi-species probiotic ingredient derived from the African opaque sorghum beer during its propagation in a starchy career model. The aim was to establish the optimum growth conditions that warrant the optimum antimicrobial activities in the product. The antimicrobial activities were tested against Gram-positive bacteria (Staphylococcus aureus ATCC 27844, S. aureus MR 825), Gram-negative bacteria (Escherichia coli ATCC 25922, E. coli O157:H7 ATCC 700728, Salmonella typhi R 30951401, Klebsiella pneumoniae ATCC 35657), as well as against yeast (Candida albicans MHMR), using agar disc diffusion method. Also, the growth of viable cells and physicochemical parameters during the propagation were monitored. The results showed that the pH and dry matter content of the probiotic ingredient decrease significantly (p˂0.05) during the propagation whereas the lactic acid, the titratable acidity, lactic acid bacteria (LAB), yeasts and moulds counts increase significantly (p˂0.05). From 0 to 12 h, the product failed to inhibit the growth of all indicator strains. From 24 h and onward, the probiotic career inhibited all indicator strains except for K. pneumoniae (ATCC 35657) which could not be inhibited. Clearly, our study showed that 36 h of the propagation were sufficient to generate a probiotic ingredient with optimum antimicrobial activities.
Keywords: Probiotic; antibiotic; opaque beer; antimicrobial activity